Rice Productivity In Bayalangu Kidul Village - hermawan, agus; Ahmad, Abdul Aziz; Istiqomah, Istiqomah (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The problem raised in this study is the decline in rice productivity. This study aimed to analyze the influence of age, education, farming experience, irrigation, activeness of farmer groups, seeds, technology and agricultural extension on rice productivity in Bayalangu Kidul Village, Gegesik District, Cirebon Regency. This study used primary data with total sample of 77 rice farmers. The method of multiple linear regressions was used in this study by processing data using eviews software. The results of the study showed that education, farming experience, irrigation, the activeness of farmer groups, seeds, and the intensity of the introduction had a positive and significant effect on rice productivity. Age and technology variables have a positive and insignificant effect on rice productivity. This finding implies that the need for the performance of local and central government in increasing rice production and farmers are expected to increase knowledge in rice farming.